PERBEDAAN PRESTASI BELAJAR ANATOMI DAN FISIOLOGI CAIRAN YANG MENGGUNAKAN METODE CERAMAH DIBANDING METODE DISKUSI PADA AKADEMI KEPERAWATAN PAMENANG - tamsuri, anas (Akademi Keperawatan Pamenang, 2010)
Anatomy and Physiology is one of the fundamental subjects for the college of nursing students, as basis to learn some of the other subjects and became one aspect of critical thinking in nursing service. However, the learning evaluation showed an average achievement of students in the learning courses are still relatively low. The purpose of this research was to find out was there a difference in student achievement that have gotten a lecture method than the method of Subject discussions on Anatomy and Physiology of Body Fluids in the Pamenang Nursing Academy. Research carried out by quasi-experimental design of two group post-test only design. Implementation of the research was from October to November 2009 (2 months). Variables include independent variable: learning methods lectures and discussions; and the dependent variable: student achievement.The results showed the value of Independent t-test calculated significance-test 0.06> p=0.05 which means that there was no significant difference in achievement between groups of students who had learning of lecture method with student who had discussion method.Keywords : learning methods lectures and discussions, student achievement